Der Wandel der niederländischen Staatsrechtswissenschaft am Ende des 19. Jahrhunderts. Über Johan Theodoor Buys (1828–1893) und seiner Deutschen Inspiration - Jansen, Corjo; Sillen, Joost Jozef Johannes (Der Staat. Zeitschrift für Staatslehre und Verfassungsgeschichte, deutsches und europäisches öffentliches Recht, 2022)
„In this article we discuss the development of Dutch constitutional law scholarship in the second half of the 19th century on the basis of the work of ‘the pope of Dutch constitutional law’ in the second half of the 19th century, the Leiden professor J.T. Buys (1828–1893). His inspiration was ‘German’. Buys praised, for instance, the work of Rudolf von Gneist (1816–1895), which was strongly influenced by the Historical School. From the end of the 1870s onwards, Buys fell under the spell of the German professor of constitutional law Paul Laband (1838–1918), especially of his seminal work Das Staatsrecht des Deutschen Reiches (1876–1882) This work had a major influence on the three-volume commentary on the Dutch constitution that Buys published between 1883 and 1888: De Grondwet. Toelichting en kritiek (‘The Constitution. Commentary and Critique’). Like Laband, Buys said farewell to a constitutional law scholarship that was overly philosophical. Instead he emphasised the independence of constitutional law as a scientific discipline. De Grondwet became the compass on which Dutch constitutional lawyers and politicians were guided for a long time. Because of Laband’s influence, Buys’ work also met with sharp criticism in the Netherlands, particularly because of its characteristic strict separation of law and practice. This criticism signaled a new phase in Dutch constitutional law scholarship.“
Keywords: Buys, Johan Theodoor (1828–1893); Deutschland; Rezeption; Staatsrecht; Verfahrensrecht

Die Rezeption des Code Civil in den nördlichen Niederlanden - Lokin, J. H. A. (Zeitschrift für europäisches Privatrecht, 2004)
Keywords: Recht; Rezeption